2018
DOI: 10.1039/c8ra02418a
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted Article: Salvianolic acid B inhibits inflammatory response and cell apoptosisviathe PI3K/Akt signaling pathway in IL-1β-induced osteoarthritis chondrocytes

Abstract: Osteoarthritis (OA) is the most common joint disease among late middle-aged or elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The cartilage tissue pieces were digested with Dulbecco's modified Eagle's medium (DMEM; Gibco) containing 0.2% collagenase and 5% foetal bovine serum (FBS; Invitrogen) overnight following with trypsin at 37°C for 10 minutes . After digestion, the cells were centrifuged at 800 r/min twice for 20 minutes and cultured in DMEM medium supplemented with 10% foetal bovine serum, 100 U/mL penicillin and 100 μg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The cartilage tissue pieces were digested with Dulbecco's modified Eagle's medium (DMEM; Gibco) containing 0.2% collagenase and 5% foetal bovine serum (FBS; Invitrogen) overnight following with trypsin at 37°C for 10 minutes . After digestion, the cells were centrifuged at 800 r/min twice for 20 minutes and cultured in DMEM medium supplemented with 10% foetal bovine serum, 100 U/mL penicillin and 100 μg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…These results align with those of Zhu et al, where SAB was reported to suppress iNOS expression, thereby mitigating inflammation and cell apoptosis in cartilage cells. 19 These findings suggest that SAB serves as an effective anti-inflammatory and antioxidant agent, preventing oxidative stress and cellular apoptosis.…”
Section: Discussionmentioning
confidence: 94%
“…It is demonstrated that the inhibition of the P13K/AKT signaling pathway contributes to the mechanisms termed apoptosis and autophagy of chondrocytes [ 42 , 43 ]. After the activation of PI3K, inositol can be phosphorylated, which promotes the activation of AKT directly or indirectly Phosphorylated-AKT is the main form of the activation of AKT [ 44 ]. P-AKT can inhibit apoptosis by suppressing the activity of FKHR, NF-kappa B and GSK-3, inhibiting phosphorylation of Bad, caspase-9 and inhibiting the release of apoptosis factors by mitochondrial [ 45 ]; it can also stimulate the TOR/P70S6‐kinase pathway to suppress the autophagy in mammalian cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%